Method for high precision reconstruction of air shower Xmax using two-dimensional radio intensity profiles - Buitink, S.; Corstanje, A.; Enriquez, J. E.; Falcke, H.; Hörandel, Jörg R.; Huege, T.; Nelles, Anna; Rachen, J. P.; Schellart, P.; Scholten, O.; Ter Veen, S.; Thoudam, S.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
The mass composition of cosmic rays contains important clues about their origin. Accurate measurements are needed to resolve longstanding issues such as the transition from Galactic to extra-Galactic origin and the nature of the cutoff observed at the highest energies. Composition can be studied by measuring the atmospheric depth of the shower maximum Xmax of air showers generated by high-energy cosmic rays hitting the Earth's atmosphere. We present a new method to reconstruct Xmax based on radio measurements. The radio emission mechanism of air showers is a complex process that creates an asymmetric intensity pattern on the ground. The shape of this pattern strongly depends on the longitudinal development of the shower. We reconstruct Xmax by fitting two-dimensional intensity profiles, simulated with CoREAS, to data from the Low Frequency Array (LOFAR) radio telescope. In the dense LOFAR core, air showers are detected by hundreds of antennas simultaneously. The simulations fit the data very well, indicating that the radiation mechanism is now well understood. The typical uncertainty on the reconstruction of Xmax for LOFAR showers is 17g/cm2.
CRIS-Team Scopus Importer:2023-08-15